How Well Do Large Language Models Support Clinician Information Needs? (Stanford HAI, 2023)
Stanford experts examine the safety and accuracy of GPT-4 in serving curbside consultation needs of doctors.
<标题>: 大型语言模型在多大程度上支持临床医生的信息需求？ Read_Status: New Read_Status_Date: 2026-01-26T11:33:34.518Z
Keywords: /unread